Penatalaksanaan Terapi Dzikir Terhadap Penurunan Tingkat Kecemasan Pada Pasien Pre Operasi : Case Report - Febi Kusuma Nugraha; Arina Maliya; Dian Setyawan (Jurnal Ners, 2025)
Introduction: Preoperative patient anxiety is an anticipatory response to a new experience that the patient may perceive as a threat to his role in life or even his life itself. Dhikr therapy (spiritual therapy) is remembering God with all His mistakes that contain spiritual elements that can generate hope and self-confidence in someone who is sick so that immunity and the healing process can increase the management of dhikr therapy on anxiety levels in preoperative patients. Purpose: The aim is to determine the management of dhikr therapy to reduce anxiety levels in preoperative patients. Method: This research design uses a quasi-experimental design with a one group pre- post test design approach without a control group. The sampling method used purposive sampling, the number of respondents was 5 respondents with predetermined inclusion and exclusion criteria. The research was conducted for 3 days at UNS Hospital Sukoharjo City, the data collection used was the ZARS (Zung Self-rating Anxiety Scale) anxiety questionnaire sheet with a practice time span from November 16 to December 22, 2023. Before being given the dhikr therapy intervention, some patients in the pre-test had moderate anxiety levels as many as 4 people and severe anxiety as many as 1 person. After being given the intervention, all patients had a mild level of anxiety as many as 5 patients. Result: Based on the results of interviews with patients who will undergo major surgery, it is found that anxiety is indeed one of the psychological problems that often arise in preoperative patients caused by various stressors. Conclusion: The management of dhikr therapy is one method of spiritual approach to patients, especially those who are Muslim, therefore this intervention is not recommended for non-Muslim patients.